Implementing Word-Coloring Media in Increasing English Vocabulary and Learning Motivation of the Year Five Pupils of SDN 27 Palu - Darmawati Darmawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study aimed to measure the effect of applying word coloring media in increasing English vocabulary and learning motivation of students at SDN 27 Palu. The sample for this quasi-experimental research consisted of students at SDN 27 Palu, including 30 students in the VA class as the experimental class and 30 students in the VB class as the control class. The sample was randomly selected. The instruments used to collect data were objective tests to measure students' knowledge of English vocabulary and a questionnaire statement to measure students' motivation in applying word coloring. The research data used the independent t-test formula by applying the degrees of freedom (df) = 58 (30+30-2) with a significant level of 0.05. The results of the t-table were 2.002. Data analysis indicated that the experimental class's mean scores had increased from 61.00 in the pretest to 78.56 in the posttest. The results of the study indicated that there was an increase in students' English vocabulary after the treatment was applied.